2018
DOI: 10.1253/circj.cj-17-0881
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results, Adverse Events, and Change in End-Organ Function in Elderly Patients With HeartMateII Left Ventricular Assist Device ― Japanese Multicenter Study ―

Abstract: plantation rule, patients aged >60 years at the time of wait list entry are been being treated nominally with bridge-totransplantation therapy (BTT) but practically with DT. To achieve better clinical results at introduction of DT in Japan, the clinical results and adverse events in these DT patients should be evaluated.In the present study, we compared the clinical results of patients aged >60 years at LVAD implantation with younger patients, and analyzed the adverse events and change of end-organ function on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…The 48-month survival rate of patients with a VAD is 49% in the United States, while it is especially high (88.7%) in Japan [ 63 , 64 ]. However, VAD implantation involves invasive thoracotomy and hospitalization, which are associated with a high risk of complications such as stroke and infection [ 65 , 66 ], especially in older patients [ 67 ]. Furthermore, although a VAD can relieve HF symptoms, such as shortness of breath and dyspnea, and improve exercise capacity, patients may continue to experience other symptoms such as physical pain, depression, and anxiety [ 68 ].…”
Section: End-of-life Care For Patients With Device Therapymentioning
confidence: 99%
“…The 48-month survival rate of patients with a VAD is 49% in the United States, while it is especially high (88.7%) in Japan [ 63 , 64 ]. However, VAD implantation involves invasive thoracotomy and hospitalization, which are associated with a high risk of complications such as stroke and infection [ 65 , 66 ], especially in older patients [ 67 ]. Furthermore, although a VAD can relieve HF symptoms, such as shortness of breath and dyspnea, and improve exercise capacity, patients may continue to experience other symptoms such as physical pain, depression, and anxiety [ 68 ].…”
Section: End-of-life Care For Patients With Device Therapymentioning
confidence: 99%
“…Subsequent innovations (axial to centrifugal flow) have not resulted in a reduction in infectious complications [7,8] with an actual increase in sepsis with the Heartware HVAD device compared to HeartMate II control [7]. Studies have looked at factors including age [22], gender [23], body habitus including both small patients [24] and obesity [25], trauma [26], duration of LVAD support [27] as well as presence of comorbid conditions such as diabetes [28][29][30], depression and chronic kidney disease (CKD) [31], alcoholism and immunosuppression [29], and malnutrition ( [32,33] and references therein). In a Japanese multicenter trial looking at 300 patients receiving HeartMate II between April 2013 and December 2016, patients older than 60 had similar overall survival and risk of driveline and pocket infections [22].…”
Section: Epidemiology and Risk Factors For Lvad Infectionsmentioning
confidence: 99%
“…Studies have looked at factors including age [22], gender [23], body habitus including both small patients [24] and obesity [25], trauma [26], duration of LVAD support [27] as well as presence of comorbid conditions such as diabetes [28][29][30], depression and chronic kidney disease (CKD) [31], alcoholism and immunosuppression [29], and malnutrition ( [32,33] and references therein). In a Japanese multicenter trial looking at 300 patients receiving HeartMate II between April 2013 and December 2016, patients older than 60 had similar overall survival and risk of driveline and pocket infections [22]. An older study found that age and the presence of diabetes were associated with increased risk of LVAD endocarditis [34] with a median age of 59 among patients with endocarditis compared with a median age of 53 in those without (p = 0.02).…”
Section: Epidemiology and Risk Factors For Lvad Infectionsmentioning
confidence: 99%
“…Использование механических устройств кровообращения приводит к улучшению функции почек у пациентов после имплантации, однако почечные исходы после трансплантации сердца, по-видимому, в большей степени зависят от уровня почечной функции, достигнутого во время имплантации LVAD, чем от базового уровня функции почек [36] [38]. При этом в случае тщательного подбора пациентов, лица старше 65 лет, получавших терапию LVAD с постоянным потоком, демонстрировали хороший уровень выживаемости [39]. В японском национальном исследовании, при сравнении группы лиц молодого возраста, с лицами старше 60 лет, через 1 и 3 года выживаемость после имплантации LVAD составляла 95%, 91% у более молодых пациентов и 85%, у 75% пожилых пациентов соответственно (Р = 0,016), хотя возраст не был фактором риска для многомерного анализа, однако, улучшение функции почек после 60 лет было временным, и улучшение длилось не более, чем 3 месяца [40].…”
Section: факторы риска и клинические исходы после имплантации Lvadunclassified